Scope Of Health Services Elderly Ages Get Health Screening According To Standards By Gender, District And Puskesmas In Dharmasraya Regency In 2021 - Syah Putra, Candra; Dian Eka Putri (Jurnal EduHealth, 2022)
Old age is a process of slowly disappearing the ability of tissues to repair and replace themselves and maintain their normal structure and function so that they cannot survive injury (including infection) and repair the damage suffered so that they cannot cope with the additional burden of stress (physical, psychological, socio, cultural economy), the importance of health service coverage will have an impact on the elderly in maintaining health status. This research method is a literature study with a secondary data approach. health center has reached 96,4% of this indicates that the role of health services in Dharmasraya district has provided optimal services for the elderly.